REGIONAL HEAD OFFICIAL APPOINTMENT MECHANISM DURING THE CONDITIONAL REGIONAL HEAD ELECTION TRANSITION PERIOD - Saparuli Saparuli; Punta Yoga (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
After the Decision of the Constitutional Court Number 14/PUU-XI/2013, ordered the General Election and Pilkada to be carried out simultaneously. since then simultaneous regional elections nationally and all aspects of its implementation have begun to be established in stages, based on Article 201 of Law no. 10 of 2016 will be implemented in 2024. This is the basis for legitimacy for the central government to appoint acting regional heads in taking control of local government. As a consequence of the implementation of the simultaneous local elections in 2024, there will be a vacancy in the post of Regional Head whose term of office expires in 2022 and 2023. Filling in positions is an important element in constitutional law. Without being filled in by officials, the functions of the follow-up position may be carried out as they should. The government needs to consider making implementing regulations, the mechanism for appointing Acting (Pj) regional heads and their authority is clear so that the appointment of these officials does not ignore democratic principles and at the same time provides guarantees for the community. This research is to find out the mechanism for the appointment and authority of Acting (Pj) Regional Heads during the simultaneous local election transition period. Normative legal research methods using statutory approaches (Statute Approach) and conceptual approaches (Conceptual Approach). The results of the study show that the Acting (Pj) is the definitive replacement for the regional head when there is a vacancy in the positions of the regional head and deputy regional head simultaneously during the simultaneous Pilkada transition period. The Acting Governor is appointed by the President through the proposal of the Minister of Home Affairs while the Acting Regent/Mayor is determined by the Minister of Home Affairs.